In vitro Polyploidisation of Neolamarckia cadamba using Colchicine - Eng, Wee Hiang (Universiti Malaysia Sarawak, 2021)
Polyploidisation has become a valuable breeding strategy of Neolamarckia cadamba to produce improved clones for planted forest development. It is a multipurpose fast-growing plantation tree species that produce high-value wood and non-wood forest products. The present study aimed to induce polyploid plants using colchicine under in vitro system and to determine the effects of in vitro polyploidisation on colchicine-induced polyploid plants of N. cadamba derived from nodal explants. The results showed that 0.3% colchicine for 48 h treatment of N. cadamba nodal segments produced the highest percentage of polyploidisation, where 20.0% were octoploids and 6.7% were mixoploids. In the flow cytometry procedure, LB01 buffer and in vitro leaf usage was crucial in obtaining reliable results, where the tetraploid DNA content was 2.59 ± 0.09 pg, while the octoploid was 5.35 ± 0.24 pg. The chromosome count procedure was optimised, namely using juvenile roots, using a combination of Feulgen and aceto-orcein 1% stains and employing double squashing. The chromosome count confirmed that the tetraploid cell of N. cadamba has 44 chromosomes while the octoploid cell has 88 chromosomes. The N. cadamba octoploid and mixoploid plants grow slower than the tetraploid under in vitro and ex vitro conditions. The leaf characteristics of N. cadamba mixoploid and octoploid plants were thicker leaf blades, thicker midrib, bigger stomata size, lower stomata density, and higher SPAD value than their progenitor. Genetic variation was detected among the mixoploid and octoploid plants using RAPD, and this result suggests that in vitro polyploidisation could be used to broaden the genetic base of N. cadamba. Collectively, this study has established an efficient protocol for in vitro induction and identification of polyploid plants of N. cadamba by colchicine treatment. The newly identified polyploid plants in the present study can potentially benefit the future breeding programme and genomics research of N. cadamba.